A Novel Pathogenic HSPG2 Mutation in Schwartz–Jampel Syndrome - Lin, Po-Yu; Hung, Jia-Horung; Hsu, Chao-Kai; Chang, Yao-Tsung; Sun, Yuan-Ting (Frontiers in Neurology, 2021)
Schwartz–Jampel syndrome is a rare autosomal recessive disease caused by mutation in the heparan sulfate proteoglycan 2 (HSPG2) gene. Its cardinal symptoms are skeletal dysplasia and neuromuscular hyperactivity. Herein, we identified a new pathogenic mutation site (NM_005529.6:c.1125C>G; p.Cys375Trp) of HSPG2 leading to Schwartz–Jampel syndrome by whole exome sequencing. This mutation carried by the asymptomatic parents was previously registered in a single nucleotide polymorphism database of the National Institutes of Health as a coding sequence variant rs543805444. The pathogenic nature of this missense mutation was demonstrated by in silico pathogenicity assessment, clinical presentations and cellular function of primary fibroblast derived from patients. Various in silico software applications predicted the mutation to be pathogenic (SIFT, 0; Polyphen‐2, 1; CADD, 23.7; MutationTaster, 1; DANN; 0.9). Needle electromyography revealed extensive complex repetitive discharges and multiple polyphasic motor unit action potentials in axial and limb muscles at rest. Short exercise test for myotonia showed Fournier pattern I. At cellular levels, mutant primary fibroblasts had reduced levels of secreted perlecan, impaired migration ability but normal capability of proliferation. Patients with this mutation showed more neuromuscular instability and relatively mild skeletal abnormality comparing with previously reported cases.